Steps connecting the courtyard to the front veranda - Mumbai Archive Project (Jio Institute, 2024)
A short flight of steps connects the courtyard (now used for parking vehicles) to the front veranda. The balusters along the handrails feature the six-pointed Star of David motif, which also features on the parapet of the veranda. On either side of the staircase are squat pedestals, which may have supported statues or planters. The helical steps in the foreground lead to a side gate opening on the veranda.